Impaired lipid profile and insulin resistance in a cohort of Austrian HIV patients. Issue 4 (April 2016) - Schulte-Hermann, Kathrin; Schalk, Horst; Haider, Bernhard; Hutterer, Judith; Gmeinhart, Bernd; Pichler, Karlheinz; Brath, Helmut; Dorner, Thomas E.
Abstract: Introduction: Traditional risk factors for cardiovascular diseases have been shown to have an even higher impact in the HIV infected population. Cardiovascular risk factors amongst people living with HIV treated in doctor's offices in Austria have not been documented before. Our study aimed to close this gap, focusing on dyslipidemia, diabetes mellitus and diabetes risk. Patients and methods: After ethics approval, consecutive patients who visited their treating physicians for routine checks were enrolled. The lipid profile was assessed by measuring total cholesterol, triglycerides, HDL and apolipoprotein B and calculating LDL and non-HDL-cholesterol. The diabetes risk was calculated by measuring insulin and blood glucose levels and assessing insulin resistance and beta cell function using the HOMA-IR model. Results: 522 patients were included in the analysis. 90.2% of the participants were on antiretroviral therapy. Two third had an impaired lipid profile, but dyslipidemia had been diagnosed only in 46.3% of the patients. There was a clear correlation between protease inhibitor use and pathologic blood lipids. Of the persons with dyslipidemia, 18.4% received lipid lowering drugs. 8 persons (1.6%) fulfilled the criteria for diabetes mellitus. Of those, 4 patients already had a diagnosed diabetes mellitus. 50.1% of the study participants showed an increased insulin resistance. Patients on nucleoside reverse transcriptase inhibitors had significantly higher markers for impaired glucose metabolism. Discussion: We found a high percentage of increased insulin resistance, of impaired lipid profile and in contrast to this a low treatment rate with lipid lowering drugs in this cohort of people living with HIV.